Clinical and molecular characterization of Hb Hofu in eastern India. (25th July 2013) - Purohit, P.; Mashon, R. S.; Patel, S.; Dehury, S.; Pattanayak, C.; Das, K.; Nair, S.; Italia, K.; Bag, S.; Colah, R.; Patel, D. K.
Summary Introduction Hb Hofu (HBB:c. 380T>A) is a rare inherited hemoglobin abnormality with few case reports in the world literature. Methods Screening for the sickle cell gene mutation and other hemoglobinopathies was carried out using the sickle slide test, Hb electrophoresis, and HPLC under an ongoing central government project. Results We detected twelve Hb Hofu heterozygotes and three sickle Hb Hofu compound heterozygotes. The heterozygotes were asymptomatic except for one individual who had chronic kidney disease and moderate anemia. Only one HbS‐Hofu case was symptomatic and presented with intermittent attacks of painful crisis. In the carrier state, the Hb Hofu eluted as a hump at the beginning of the HbA0 window. But in HbS‐Hofu cases, Hb Hofu eluted as a single peak in the HbA0 window, with the HbA2 levels being >4% consistently. Conclusion HbS‐Hofu has a variable clinical presentation. The retention time of Hb Hofu on HPLC is very close to that of HbA0 and often elutes in the A0 window. Thus, there is every possibility of the HbS‐Hofu chromatogram to be misinterpreted as that of a sickle cell trait/transfused sickle cell‐beta‐thalassemia case. This is the first time where Hb Hofu has been detected by HPLC, which is the widely accepted screening technique for hemoglobinopathies around the world.